Mucus Penetrating and Cell‐Binding Polyzwitterionic Micelles as Potent Oral Nanomedicine for Cancer Drug Delivery. Issue 16 (13th March 2022) - Fan, Wufa; Wei, Qiuyu; Xiang, Jiajia; Tang, Yisi; Zhou, Quan; Geng, Yu; Liu, Yanpeng; Sun, Rui; Xu, Lei; Wang, Guowei; Piao, Ying; Shao, Shiqun; et al.
Abstract: Orally administrable anticancer nanomedicines are highly desirable due to their easy and repeatable administration, but are not yet feasible because the current nanomedicine cannot simultaneously overcome the strong mucus and villi barriers and thus have very low bioavailability (BA). Herein, this work presents the first polymeric micelle capable of fast mucus permeation and villi absorption and delivering paclitaxel (PTX) efficiently to tumors with therapeutic efficacy even better than intravenously administered polyethylene glycol based counterpart or free PTX. Poly[2‐( N ‐oxide‐ N, N ‐diethylamino)ethyl methacrylate] (OPDEA), a water‐soluble polyzwitterion, is highly nonfouling to proteins and other biomacromolecules such as mucin but can weakly bind to phospholipids. Therefore, the micelle of its block copolymer with poly(ε‐caprolactone) (OPDEA‐PCL) can efficiently permeate through the viscous mucus and bind to villi, which triggers transcytosis‐mediated transepithelial transport into blood circulation for tumor accumulation. The orally administered micelles deliver PTX to tumors, efficiently inhibiting the growth of HepG2 and patient‐derived hepatocellular carcinoma xenografts and triple‐negative breast tumors. These results demonstrate that OPDEA‐based micelles may serve as an efficient oral nanomedicine for delivering other small molecules or even large molecules. Abstract : Mucus penetrating and cell‐binding polyzwitterionic micelles are developed as potent oral nanomedicine for cancer drug delivery.